2014
DOI: 10.1159/000362381
|View full text |Cite
|
Sign up to set email alerts
|

The J-Curve in Arterial Hypertension: Fact or Fallacy?

Abstract: It is known that a large proportion of patients with arterial hypertension are undertreated. This may result in an increase of the incidence of cardiovascular events. On the other hand, aggressive reduction of blood pressure may increase cardiovascular events (J-curve phenomenon) in certain populations. This phenomenon may be seen in patients with coronary artery disease and left ventricular hypertrophy when the diastolic blood pressure decreases below 70-80 mm Hg, and the systolic blood pressure decreases bel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…Even in the presence of diabetes and other risk factors, no reason exists to adopt an aggressive blood-pressure-lowering treatment, as previously suggested. A meta-analysis showed that in patients with diabetes and a baseline systolic blood pressure level <140 mmHg, further blood-pressure lowering resulted in an increased risk of cardiovascular death 73 (FIG. 4).…”
Section: Guideline Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even in the presence of diabetes and other risk factors, no reason exists to adopt an aggressive blood-pressure-lowering treatment, as previously suggested. A meta-analysis showed that in patients with diabetes and a baseline systolic blood pressure level <140 mmHg, further blood-pressure lowering resulted in an increased risk of cardiovascular death 73 (FIG. 4).…”
Section: Guideline Recommendationsmentioning
confidence: 99%
“…No validated threshold exists for high versus low blood pressure in patients with coronary artery disease. Considering the available data, a threshold of 130 mmHg systolic and 80 mmHg diastolic is reasonable 72,73 . In patients with lower blood pressure, the use of ivabradine (if associated with a concomitant increase in heart rate), ranolazine, or trimetazidine is preferable (FIG.…”
Section: Guideline Recommendationsmentioning
confidence: 99%
“…A faster heart rate during therapy for hypertension may be associated with adverse events, regardless of the extent of changes in blood pressure. Thus, the so-called J-curve phenomenon in arterial hypertension may at least partially be related to an increase in heart rate and not only to changes in blood pressure [54]. …”
Section: Heart Rate and Survival After Therapeutic Interventionsmentioning
confidence: 99%
“…Although there is not a validated threshold dividing SCHD patients into a high and low BP levels, a threshold of 120 mmHg in systolic blood pressure can be used as a reference [83,84]. Some have recently advocated a threshold of 100 mmHg of systolic blood pressure, below which not to further push treatment with antianginal drugs that have vasodilating properties [85] ).…”
Section: Blood Pressurementioning
confidence: 99%